Fast encirclement of an exceptional point for highly efficient and compact chiral mode converters - Xiaoqian Shu (Nature Communications, 2022)
Chiral mode converters are found in a wide range of practical applications in optics, but the previous proposals suffer from low efficiency and large device size. Here the authors propose a highly efficient and compact chiral mode converter based on encircling exceptional points along Hamiltonian parameter space boundary, relaxing the adiabaticity constraints.